Więź z Bogiem według czwartej Ewangelii - Gryglewicz, Feliks (The Biblical Annals, 2017)
Aiming at the characterization of John’s approach to the relationships of the faithful and God, the author has discussed the connections of the listeners and the faithful with Jesus, the unification of Jesus and God the Father as well as the triangular mutual bonds of God the Father, Jesus Christ and the faithful, and then the meaning of the expressions meno en and eimi en, as well as the participation of particular persons in the bonds.